GLOBAL ENGLISH: CHALLENGES AND OPPORTUNITIES IN THE 21ST CENTURY. (Ustozlar uchun, 2025)
In the 21st century, English has become a global language used in international communication, education, business, and technology. The widespread use of English creates many opportunities, such as global collaboration, access to information, and academic mobility. However, it also presents challenges, including language inequality, the dominance of native speakers, and the threat to linguistic diversity. This article examines the major challenges and opportunities of Global English and discusses its impact on education and cross-cultural communication in the modern world.